Parâmetros vocais perceptivo-auditivos e acústicos em crianças com nódulos vocais - Gramuglia, Andrea Cristina Jóia [UNESP] (2013)
Vocal nodules constitute the major causes of dysphonia during childhood. Auditoryperceptual and acoustic vocal analyses have been used to differentiate voice with nodules from normal voice in children. To study the value of auditory-perceptual and acoustic vocal analyses in assessments of children with nodules. A comparative study was carried out including 100 children aged between 4 and 11 years, with videolaryngoscopic diagnosis of vocal nodules (nodule group), and 100 children within the same age range, without vocal symptoms and with normal videolaryngoscopic exams (control group). All children were subjected to auditory-perceptual vocal analyses (GRBASI scale), calculation of Maximum Phonation Time and s/z ratio, and acoustic vocal analysis (MDVP software). There was no difference in the values of maximum phonation time and s/z ratio between groups. Auditory-perceptual analysis indicated greater compromising of voice parameters for the nodule than for the control group: G (79 versus 24), R (53 versus 3), B (67 versus 23) and S (35 versus 1). The acoustic parameters jitter, PPQ, shimmer, APQ, NHR and SPI showed higher values in the nodule than in the control group. The parameter f0 did not differ between groups. Auditory-perceptual (G, R, B and S) and acoustic vocal parameters (jitter, PPQ, shimmer, APQ, NHR and SPI) were more compromised for children with nodules than for those of the control group, constituting important methods for assessing child dysphonia